Dhvar5 antimicrobial peptide (AMP) chemoselective covalent immobilization results on higher antiadherence effect than simple physical adsorption - Fabiola M T A Costa (2015)
Bacterial colonization and subsequent biofilm formation is still one of the major problems associated with medical devices. Antimicrobial peptides (AMP) immobilization onto biomaterials surface is a promising strategy to avoid bacterial colonization. However, a correct peptide orientation and exposure from the surface is essential to maintain AMP antimicrobial activity. This work aims to evaluate the effect of the immobilization on antibacterial activity of Dhvar5 (LLLFLLKKRKKRKY), an AMP with a head-to-tail amphipathicity. Dhvar5 was linked to thin chitosan coatings in i) a controlled orientation and exposure, testing covalent immobilization of its N- or C-terminus and using spacers with different lengths and flexibilities or in ii) a random orientation by physical adsorption. Chitosan coating was chosen due to its antimicrobial properties and readiness to be functionalized. Surface characterization demonstrated the chemoselective immobilization of the peptide with different spacers in a similar concentration (similar to 2 ng/cm(2)). Efficacy assays demonstrated that covalent immobilization of Dhvar5 exposing its cationic end, improves the chitosan coating antimicrobial effect by decreasing Methicillin-resistant Staphylococcus aureus (MRSA) colonization. This effect was enhanced when longer spacers were used independently of their flexibility. In opposite, immobilized Dhvar5 exposing its hydrophobic end has no effect on bacterial adhesion to chitosan, and when adsorbed in a random orientation even induces bacterial adhesion to chitosan coating.